(3QSGdI aj EYQGH GdCOhjIs
(3ChdgG (B:s
(3aj GdCda GdeaJhMI (B: (3CQGOQNJ , BS , Cfc CPQHhf , BPGf GdaGQ, CHfhS , CHchf, EHQjSe s
(3BNQgG (B:s
(3GdZjf GdecShQI (B: (3ZjQH , ZQGA GdLdhO , ZQGA GdSec , ZQGA TLQ GdJaGM GdceKQi s
(3Vef eLehY , JQJjHgG (B: (3ef U (B133 - (3U(B138s
(3GfXQgG eY GdeQTO ddQGRj Qbe (B"730"s
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA WH (B- (3bSe GdcJGH GdKGfi (B- (3U (B103 s
Keywords: (3GdWHs